IMPLEMENTATION OF WEBQUAL 4.0 FOR MEASURING WEBSITE QUALITY FOR USER SATISFACTION: (A Case Study on University Polytechnic of Hauts-de-France) - Setiawan, Arliza Chairani; Lestari, Baroroh (Transpublika Publisher, 2024)
Universities strategically utilize their websites as potent tools for branding and marketing initiatives, enabling them to highlight academic programs, showcase on-campus achievements, and disseminate crucial information, such as admission details, to potential students. This study focuses on evaluating the quality of the University Polytechnic of Hauts-de-France IUT Department website, emphasizing User Satisfaction. The assessment employs the WebQual 4.0 methodology, encompassing three pivotal dimensions: Usability Quality, Information Quality, and Service Interaction Quality. The research methodology employed in this study was hypothesis testing with the population and sample consisting of 31 students, using the census technique. The research findings underscore the substantial impact of both Information Quality and Usability dimensions on website users. Areas for improvement based on the study include enhancing Service Interaction Quality with more personalized features, ensuring Information Quality with updated and relevant content, and optimizing Usability Quality by improving website navigation and accessibility. The implementation of these improvements holds the potential to positively influence User Satisfaction, reinforcing the pivotal role that website quality plays in shaping the overall perception of a university. This study reinforces the importance of user-centric improvements to enhance the overall effectiveness of university websites in meeting the evolving expectations of users in the digital era.